Household risky financial asset allocation in China: The influence of financial literacy dimensions - LinXi Shi; Thien Sang Lim (EnPress Publisher, LLC, 2024)
The rise of financial inclusion has notably increased household engagement in risky financial asset allocation, posing challenges to macro-financial stability. This study explored the crucial role of financial literacy in enabling households to effectively engage with complex financial markets and products. Specifically, it examined how different aspects of financial literacy—knowledge, attitudes, and skills—influence both the participation and depth of household investment in risky financial assets in China. Utilizing a comprehensive dataset from the 2019 China Household Finance Survey, which included 32,458 households, this study employed a robust indicator system and regression analysis via STATA 17.0 to assess these impacts. The results demonstrated that enhancements in financial literacy significantly foster increased engagement and deeper involvement in risky asset allocation, particularly through improved financial attitudes. Additionally, the analysis revealed that households led by women show a higher propensity towards risky asset investments than those led by men. These insights suggested the potential for targeted financial education to improve the financial health and economic resilience of Chinese households.